Prevalence of transmitted drug resistance among HIV-1 treatment-naive patients in Beijing. Issue 3 (18th January 2018) - Song, Y.X.; Xin, R.L.; Li, Z.C.; Yu, H.W.; Lun, W.H.; Ye, J.; Liu, A.; Li, A.X.; Li, J.W.; Ye, J.Z.; Hao, M.Q.; Lu, H.Y.; et al.
Abstract: To optimise patients' outcomes and gain insight into transmitted drug resistance (TDR) among human immunodeficiency virus (HIV)-1 treatment-naive patients in Beijing, the prevalence of TDR was assessed. Demographic and clinical data of 1241 treatment-naive patients diagnosed between April 2014 and February 2015 were collected. TDR was defined using the Stanford University HIV drug resistance mutations database. The risk factors were evaluated by multi-logistic regression analysis. Among 932 successfully amplified cases, most were male (96.78%) and infected through men having sex with men (91.74%). Genotype were CRF01_AE (56.44%), B (20.60%), CRF07_BC (19.96%), C (1.61%) and other genotypes (1.39%). The overall prevalence of TDR was 6.12%. Most frequent mutations occurred in non-nucleoside reverse transcriptase inhibitors (NNRTIs) (3.11%), followed by protease inhibitors (PIs) (2.25%) and nucleoside reverse transcriptase inhibitors (NRTIs) (1.32%). Furthermore, HIV-1 genotype was associated with high risk of resistance, in which genotype C and other genotype may have higher risk for resistance. The prevalence among treatment-naive patients in Beijing was low. Resistance to NNRTIs was higher than with PIs or NRTIs. Continuous monitoring of regional levels of HIV-1 TDRs would contribute to improve treatment outcomes and prevent failures.